The Health Care Quality Challenge and the Clinical Nurse Leader Role (CNL) - Marietta Stanton (Rural Nurse Organization; Binghamton University, 2006)
In 2001, the Institute of Medicine (IOM) released the report Crossing the Quality Chasm: A New Health System for the 21st Century (Institute of Medicine 2001). Based on a large body of evidenced documenting severe problems in the American health care system, the report identifies six aims for quality improvement. These are that health care should be: 1. Safe-prevents harm to patients (Institute of Medicine, 2004). 2. Effective-refers to care that is evidence-based (Institute of Medicine, 2001). 3. Patient-centered-addresses care that reflects the qualities of compassion, empathy and responsiveness to the needs values, and expressed preferences of the individual patient (Institute of Medicine, 2001). 4. Timely-considers access to care as a critical factor influencing the quality of rural health care (Institute of Medicine, 2001). 5. Efficient-refers to optimizing resources and minimizing waste to obtain the best value for investments in health care services and administration (Institute of Medicine, 2001). 6. Equitable- ensures that the availability of care and quality services are based on an individual's health care needs and not on personal characteristics such as gender, ethnicity, geographic location, and socioeconomic status (Institute of Medicine, 2001).